2021
DOI: 10.3390/v13040679
|View full text |Cite
|
Sign up to set email alerts
|

A New Strain of Virus Discovered in China Specific to the Parasitic Mite Varroa destructor Poses a Potential Threat to Honey Bees

Abstract: The ectoparasitic mite, Varroa destructor, feeds directly on honey bees and serves as a vector for transmitting viruses among them. The Varroa mite causes relatively little damage to its natural host, the Eastern honey bee (Apis cerana) but it is the most devastating pest for the Western honey bee (Apis mellifera). Using Illumina HiSeq sequencing technology, we conducted a metatranscriptome analysis of the microbial community associated with Varroa mites. This study led to the identification of a new Chinese s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 75 publications
(58 reference statements)
1
9
0
1
Order By: Relevance
“…The read counts were on average 7,441-fold and 21-fold higher in V. destructor than in bees, respectively. Other researchers have observed similar results to ours, with both present but without evidence of replication in bees 11 , 69 . Their presence in bees seems to be related to feeding by the mite 3 wherein they acquire a small number of viral particles.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The read counts were on average 7,441-fold and 21-fold higher in V. destructor than in bees, respectively. Other researchers have observed similar results to ours, with both present but without evidence of replication in bees 11 , 69 . Their presence in bees seems to be related to feeding by the mite 3 wherein they acquire a small number of viral particles.…”
Section: Discussionsupporting
confidence: 90%
“…Work on Middle East and African honey bees has also shown a high viral diversity in V. destructor relative to their bee hosts. Other RNA-Seq studies from Asia have similarly identified new viruses prevalent in V. destructor , sometimes demonstrating a V. destructor virus to be present and replicating in associated honey bees 10 , 11 . DNA viruses have similarly been recently discovered in mites 12 , 22 , 35 , some of which they may passively acquire from feeding on bees 36 .…”
Section: Introductionmentioning
confidence: 89%
“…RNA-seq is a powerful tool that has been widely used to analyze the composition of known viruses, discover novel RNA viruses, and detect pathogenic viruses [22,45,46]. Many studies have focused on the viromics of honeybees using sequencing methods, significantly improving the scientific understanding of bee viruses [23,26,[47][48][49][50]. Far fewer studies have been performed on wild insect pollinators, although their survival is also threatened by viruses [7,[51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…This includes the discovery of previously unknown RNA viruses in house crickets (Acheta domesticus) [1], soybean thrips (Neohydatothrips variabilis) [2], termites [3], dung flies (Scathophaga furcata) [4], mosquitoes (Aedes aegypti) from the Amazon basin [5], hematophagous arthropods (including mosquitoes, ticks, and bedbugs) from Serbia [6], honey bees (Apis mellifera) [7][8][9] and wild bee species (Andrena spp.) [7], and even Varroa destructor mites, which are closely associated with both Western and Eastern honey bees (Apis mellifera and A. cerana, respectively) [10]. Reports of the discovery and analysis of novel DNA viruses, including nudiviruses of corn rootworms (Diabrotica undecimpunctata and D. virgifera) [11] and a betabaculovirus from the moth Matsumuraeses phaseoli, an important legume pest, were also presented [12].…”
mentioning
confidence: 99%
“…Sequence data on the novel viruses identified in high-throughput sequencing studies could be a starting point for further analysis of virus-host interactions. Notably, some of the published papers already present such analyses, including the investigation of viral inter-species transmission between wild and managed honey bees [7] and between the mites V. destructor and honey bees (A. mellifera) [10], and analysis of virus-derived small interfering RNAs providing an insight into antiviral RNA responses [4].…”
mentioning
confidence: 99%